2007
DOI: 10.1152/ajpgi.00117.2007
|View full text |Cite
|
Sign up to set email alerts
|

HETEs enhance IL-1-mediated COX-2 expression via augmentation of message stability in human colonic myofibroblasts

Abstract: Proinflammatory cytokines and eicosanoids are central players in intestinal inflammation. IL-1, a key cytokine associated with intestinal mucosal inflammation, induces COX-2 expression in human colonic myofibroblasts (CMF) and increased prostaglandin E(2) secretion is associated with inflammatory bowel disease (IBD) and colorectal cancer (CRC). We have previously demonstrated that IL-1alpha-induced cyclooxygenase-2 (COX-2) expression is the result of NF-kappaB- and ERK-mediated transcription, as well as COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 80 publications
3
29
0
Order By: Relevance
“…47 Studies examining the ability of lenalidomide or related drugs to stabilize RNA are limited, although in colon cancer cell lines, thalidomide has been shown to diminish COX2 mRNA stability via shuttling of HuR. 48 Further study of the mechanism of CD154 mRNA stabilization by lenalidomide in CLL and the kinetics of this process warrant further study that is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…47 Studies examining the ability of lenalidomide or related drugs to stabilize RNA are limited, although in colon cancer cell lines, thalidomide has been shown to diminish COX2 mRNA stability via shuttling of HuR. 48 Further study of the mechanism of CD154 mRNA stabilization by lenalidomide in CLL and the kinetics of this process warrant further study that is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is not possible to determine from these studies whether the reduction in free metabolites of arachidonic and linoleic acids occurred because of a reduction in substrate (e.g., free arachidonic acid), a decrease in lipoxygenase and cyclooxygenase activities, or a reduction in the activities of other enzyme pathways or whether the decrease resulted from the binding and removal of the final stable products of these pathways. It has been reported that the latter can interact to enhance the former ( 12,13 ), making the distinction diffi cult to determine. These many possibilities need to be addressed by future studies.…”
Section: Female Ldlrmentioning
confidence: 99%
“…These studies have investigated various cell types (both primary and cultured), including monocytes, colonocytes and myofibroblasts, but also include a host of animal studies where IBD-like inflammation was induced. Through the signalling pathways outlined previously, inflammatory responsesmainly cytokine production and inflammatory cell infiltration -have been shown to be attenuated by usage of specific inhibitors against p38 and JNK [27,35,38,44,52,63].…”
Section: Therapeutic Relevance Of Map Kinase Inhibitors?mentioning
confidence: 99%